Evaluating the Predictive Role of Attachment Style, Love Attitude and Spiritual Intelligence on Quality of Life - Vyas, Freya; Mishra, Khushboo Ashokkumar (Utan Kayu Publishing, 2026)
Quality of life (QoL) is shaped by a complex interplay of relational and psychological processes, yet the integrated contribution of attachment styles, love attitudes, and spiritual intelligence remains insufficiently understood, particularly in non-Western contexts. The present study examined the predictive role of these constructs in a sample of 201 young adults (18–30 years) in India. Participants completed standardized measures of attachment, love attitudes, spiritual intelligence, and QoL. Data were analysed using hierarchical multiple regression to assess the incremental contribution of each set of predictors. Attachment styles significantly predicted QoL in the initial model, with anxious attachment negatively associated and dependent attachment positively associated with QoL. The inclusion of love attitudes explained additional variance, with eros and pragma emerging as negative predictors and mania as a positive predictor. In the final step, spiritual intelligence contributed significant incremental variance, with personal meaning production and conscious state expansion emerging as positive predictors. However, in the combined model, only selected predictors retained significance, indicating substantial shared variance across constructs. These findings suggest that quality of life is best understood as an outcome of interacting relational and meaning-making systems, where attachment-based regulation and existential resources play a more foundational role than romantic attitudes alone. The results are discussed in light of attachment theory, meaning-making frameworks, and the cultural context of emerging adulthood in India.